Diam yang Menggerogoti: Suara Perempuan dalam Dua Cerpen Terpilih karya Sasti Gotama - Diantri Seprina Putri; Titis Kusumaningrum Witdaryadi Putri (Lingua Susastra, 2023)
Women's voices about their experiences of being a wife and mother are still often underestimated. This is due to the idea that it is indeed a woman's nature to make sacrifices and to prioritize her family's happiness above her own. This isue is also expressed in two short stories “Apa Yang Paul McCartney Bisikkan Kepada Janitra?” and “Pembersih Jejak Kematian” by Sasti Gotama. The purpose of this study is to reveal the voices of women in the short stories and draw meaning from them. This research is a qualitative using descriptive analysis method. The data was collected from the text of “Apa Yang Paul McCartney Bisikkan Kepada Janitra?” and “Pembersih Jejak Kematian”. The data was analyzed by using the theory of feminism. Furthermore, the meaning was revealed through text interpretation. The results showed that Apa “Apa Yang Paul McCartney Bisikkan Kepada Janitra?” and “Pembersih Jejak Kematian”  expressed women's voices in the form of experiences as a mother and wife in the household which are shown through the main female characters, Janitra and Hantu Hujan. The analysis showed that these short stories speak for women's voices so that they can get proper appreciation and understanding for all their efforts and sacrifices as a wife and mother for their family